Miller Fisher syndrome and Guillain-Barré syndrome: dual intervention rehabilitation of a complex patient case. (2nd January 2022) - Mayer, Jill E.; McNamara, Christine A.; Mayer, John
ABSTRACT: Purpose : Guillain-Barré syndrome (GBS) presents with acute peripheral neuropathy leading to ascending motor and sensory deficits. Miller Fisher syndrome (MFS), a GBS variant, is characterized by ophthalmoplegia, ataxia, and areflexia. In unusual cases, MFS and GBS overlap. The purpose of this case report is to illustrate the effects of an aquatic and land-based physiotherapy (PT) intervention on a patient with MFS-GBS. Case Description : A 57-year-old male physician was diagnosed with complex regional pain syndrome following a quadriceps muscle tear. Within 1 month, the patient experienced evolving motor, sensory, autonomic, and cranial nerve dysfunction and was diagnosed with MFS-GBS. Interventions : Five months post-onset, a 7-week intensive PT program was initiated including aquatic and land-based interventions. Outcomes : Following completion, functional improvements were demonstrated on the 6 Minute Walk Test, Timed-Up-and-Go, 10 Meter Walk Test and Short Form-36. However, 6 weeks after program completion, the patient had a recurrence. Conclusion : PT intervention demonstrated improvement in functional outcomes for a patient with a diagnosis of MFS-GBS. Complex patients lacking recovery within 6 months may benefit from continued rehabilitation. Other intervention approaches may need to be considered, including aquatic therapy.